Adultescência e imagem: o emergir do puer aeternus" nos meios de comunicação - Escudero, Andreia Perroni (2012)
Currently, there are many factors that prove that the contemporary adult (especially in large capitalist cities) has habits, behavior and attitudes that are adultescent like. This research assumes that the media have an essential role in creating standards for the youth (standardization) that serve as reference for these adults, encouraging a demand for products that highlight this trend by providing identity to them according to the behaviors that the marketers assume to be more interesting to be spread in the media(economically speaking). The main objective of this research is to analyze the role of media in the creation and proliferation of the aesthetic kidult culture among individuals from 25 to 40 years old concurrently with the need of reinforcing this behavior as a lifestyle that generates profits. However, to achieve this analysis it was necessary to go deep inside another factor: the youth has its own universal and secular charms and therefore the need to bring the archetypal aspects of the puer aeternus, because they end up reflected in the media content and in the processes of identification and projection that are part of the individuals. The chosen research method was the exploratory one with the study of multiple cases, so that the objects of study are fragments of cinematographic or television productions and the printed media and internet media that determine the youth aesthetics and the behavior reproduced by the kidults . Considering that to address the concept of self-reference in the media, the self-image construction, visibility crisis and the iconophagy are the essence of this research, this analysis will be conducted based on the thoughts of the communication theorist Norval Baitello. The theorists Bystrina, Bauman, Debord, and Postman will perform in this study the intersection among the culture of the masses, the consumption logic and the communication field. To better understand the thoughts and the attitudes of the "puer," we will count mainly on the work of the psychotherapists Contardo Calligaris, Marie Louise Von Franz, James Hillman and Charles Melman